MRAS Speed Sensorless Vector Control of Induction Motor Drives using Predictive Adaptation Mechanism - Moustafa Zair; Abdeldjebar Hazzab (Institute of Advanced Engineering and Science, 2018)
Recently of the main topic of research is the sensorless vector control of induction motor drive, In this paper presents the predictive model reference adaptive system (PMRAS) rotor speed observer, This observer developed from the classical MRAS rotor flux scheme associated with predictive adaptation mechanism designed from the Finite Control Set Model Predictive Control (FCS–MPC) by using a search optimization algorithm for calculate the rotor position which guarantee a minimum speed tuning error signal at each sampling period. The effectiveness of the proposed observer proved with the simulation results, show high dynamic performance speed and position observed in sensorless vector control process at low and zero speed as well robustness against motor parameter variation with different loading conditions.